Apologizing in the Makassar Language: A Cross-Cultural Comparison Study on Politeness Strategies - Burhanuddin Burhanuddin; Muhammad Arham (Fakultas Sastra - Universitas Muslim Indonesia, 2017)
PThis study aims to find variations in the language used by a group of people, especially the Ma-kassar language. The author is interested in finding several ways to apologize in the Makassarlanguage in the context of different situations. The author uses semi-structural interviews inobtaining the data, and has interviewed 3 (three) people who work in the field of culture andhistory at the Lagaligo Museum in the South Sulawesi Archaeological Office. The data foundhas shown that it is interesting to know a number of ways to apologize in the Makassar languageand in different situations, and integrated with language items, speech communities, languagevariations and standard languages. And the most prominent is the variety of languages used inapologizing such as visiting someone, eating and drinking, social interactions such as marriage,apologizing for an error, and others.